Effect of exposure to environmental phenols and parabens on folate concentrations among 3–19 years old children and adolescents: A cross-sectional study in NHANES 2005–2016 - Meng Ni; Zhenying Lin; Ze Chen; Ziwen Xu; Qianqian Zhang; Jiuru Zhao; Wei Li; Yanan Tang; Zelin Cao; Baihe Li; Dongting Yao; Chunyu Cheng; et al. (Ecotoxicology and Environmental Safety)
Phenols and parabens, as endocrine-disrupting chemicals (EDCs), are prevalent in daily consumer products and industrial applications. Folate, a vital vitamin, plays a crucial role in numerous metabolic processes. The interaction between EDCs and folate is not well understood and warrants investigation. We utilized data from the National Health and Nutrition Examination Survey (NHANES) 2005–2016. Since many pollutants are co-exposed congeners, with interactive effects between pollutants, we employed multivariate linear regression model, weighted quantile sum regression, and Bayesian kernel machine regression (BKMR) to quantify the impact of folate levels in serum and red blood cell (RBC) and the overall effects of combined exposures. The study included 4395 children and adolescents. A negative correlation was observed between RBC folate concentrations and urinary concentrations of Bisphenol A (BPH), Triclosan (TRS), Methyl paraben (MPB), Propyl paraben (PPB), and Butyl paraben (BUP), in children and adolescents. Specifically, an increase in RBC folate levels was linked to a decrease in urinary BPH, TRS, MPB, PPB, and BUP concentrations. Similar associations were found with serum folate. The weighted quantile sum index showed a decrease in both RBC and serum folate levels with an increase in the mixture of phenols and parabens. BKMR further supported the overall negative impact of the chemical mixture on folate levels. This study provides evidence of an inverse relationship between exposure to phenols and parabens and folate concentrations in children and adolescents, which would be of significance in providing guidance for clinical interventions and calling for remediation actions to be prioritized during childhood.